The Constancy of the Wage Share: The Canadian Experience - Hotson, John H. (The Review of Economics and Statistics, 1963)
P HE controversy over stability or lack of stability of relative shares continues unresolved. Good men and true among our colleagues, such as G. J. Schuller (io), D. G. Johnson (5), E. H. Phelps-Brown and M. H. Browne (8), R. M. Solow (i i), and I. B. Kravis (6), take a hard look at pretty much same data, allocate a few accounts differently, and come up with widely diverging answers. Johnson and Phelps-Brown and Browne see stability, rigidity, fixity. Solow and Kravis, however, take issue with those who, in Solow's spritely phrase hold view that, the share of national income accruing to labor one of great constants of nature, like velocity of light or incest taboo. (ii) New interest and significance has been injected into this controversy of late by S. Weintraub (I4), (I6) who forcefully restates contention that labor's share analogous to a natural constant like law of gravity or Senator Goldwater's views on taxation. On this fixity he erects a wage cost mark-up equation to replace venerable equation of exchange and a law of price level with strong wage push inflation implications. Weintraub shifts discussion from labor's share of National Income to labor's share of Business Gross Product, or rather its reciprocal which he dubs k, and concludes that the practical constancy of k an empirical fact, [(I4), 39] and further holds that k's constancy is probably most important law, in true sense, that economists have to work with. [(I4), 33] A. P. Lerner's review article (7) concedes this constancy, but deplores Weintraub's excitement over this near fixity and his building a Law of Price Level on it. I cannot decide for others such a question as how big a fluctuation a small fluctuation, but if Solow, Kravis and others, like Lerner, will accept k as practically constant, it would appear that rest of what Weintraub has done, including getting excited, follows logically. Acceptance of a truly constant wage share as fact calls for much recasting of distribution and price theory and a basic policy change. Some sort of wage control machinery would become our chief weapon to fight inflation rather than our present reliance on monetary policy. As indicated by its title, this paper a study of statistics on labor's share in Canada. I hope that similarities and contrasts developed between Canadian and United States experience will resolve some of points at issue in this controversy. Since it Weintraub's formulation which has given fresh interest to topic I shall follow his lead in concepts and presentation. Because it somewhat easier to think in terms of percentages than of mark-ups, however, I shall include percentages also. Weintraub defines k as ratio of gross product (Z) to employee compensation (W) and takes as empirical measures of them U.S. Department of Commerce series Business Gross Product (BGP) and Compensation of Business Employees (Wb). Thus symbolically;